Checklist and taxonomic notes on amphibians of the Western Ghats (Zoological Records and Reviews, 2022)
The Western Ghats of peninsular India is one of the world's eight recognised biodiversity hotspots and constitutes themost amphibian-diverse region in Asia, supporting over 190 endemic species across multiple family-level lineages foundnowhere else on Earth. Despite intensive taxonomic activity over the past two decades, the cumulative species checklistfor Western Ghats amphibians remains scattered across numerous publications with inconsistent nomenclature andincomplete distributional data. This study presents a comprehensive, critically annotated checklist of amphibians of theWestern Ghats based on systematic review of all published literature to December 2021, supplemented by original fielddata from 124 survey localities collected between 2017 and 2021. We recognise 268 valid amphibian species from theWestern Ghats, comprising 242 anurans across 14 families, 20 caecilians across 2 families, and 6 salamanders of thefamily Hynobiidae. The checklist incorporates 18 new species described since the most recent prior synthesis (Frost2020), resolves 24 nomenclatural issues, and provides updated distributional data for 84 species. Endemism isexceptionally high at 78.4% (210 species). Molecular phylogenetic analysis of 48 selected species using 16S rRNA andcytochrome b confirms the distinctiveness of 6 candidate new species identified during field surveys. IUCN conservationstatus is assessed for all species, with 112 (41.8%) classified as Threatened. The checklist provides the most current andcomprehensive taxonomic inventory of Western Ghats amphibians available and serves as an essential reference forconservation planning and future systematic research.